Implementasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Pendidikan Agama Islam untuk Membentuk Sikap Toleransi Siswa di SMAN 2 Sape - Chaisar, Muhammad; Nasaruddin, Nasaruddin; Kaharuddin, Kaharuddin (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2025)
This study aims to describe the implementation of religious moderation values ​​in the learning process of Islamic Religious Education (PAI) at SMAN 2 Sape and analyze its influence on the formation of students' attitudes of tolerance. This study uses a qualitative approach with a descriptive method, while data collection techniques are carried out through observation, in-depth interviews, and documentation studies. The results of the study indicate that PAI subject educators at SMAN 2 Sape actively integrate the principles of religious moderation in the learning process, including the values ​​of tolerance, rejection of violence, commitment to national integrity, and respect for diversity. The implementation of these values ​​has been proven to provide a positive contribution to the formation of inclusive student characters, respecting differences, and upholding the values ​​of diversity. Based on these findings, the study recommends the need to strengthen contextual, dialogical, and inclusive learning strategies to support the internalization of religious moderation values ​​and foster a tolerant attitude in students in a sustainable manner.